Operation, Administration and Maintenance of Municipal Fiber Networks - Oskar Januschke; Jakob Egg; Michael Mairhofer; Thomas Wimmer; Wolfgang Reichl; Ernst-Olav Ruhle (International Telecommunications Society (ITS), 2017)
The region of Lienz in Eastern Tyrol is a pioneer in municipal broadband networks and the activities take place in a state which itself also has a pioneering role in terms of how the public sector understands broadband issues. Over the last years, the 15 municipalities in the area of Lienz have initiated a project against the background of the following setting: 1. The municipalities in the region have taken the responsibility for deploying the passive network (ducts and fibers) based on a FTTB(H concept, partly supported by state aid. 2. The municipalities are confronted with a large number of tasks for the deployment and the operation and maintenance of the network. The selection of network providers for the active network and the provision of services has attracted wider interest. 3 active operators ensure competition in the end user market. The key aspects that remain as tasks for the municipality are network operation, maintenance, installation, fault repair, inspection and documentation. A number of lessons learnt can be listed especially with respect to processes for network deployment, maintenance, inspection etc. Municipalities have to dive into detailed operational details in order to achieve successful project results. Such detailed aspects of the project contain e.g. the fiber concept, the connections to the buildings, a delineation between tasks of operators and municipalities, inspection, documentation and operation and maintenance. A key factor is that projects tend to be small and struggle to achieve economies of scale
Keywords: 330